인도양 중앙해령 Daum 열수분출대의 광물·지구화학적 연구 - 김령균; 최선기; 김종욱; 박상준; 김원년 (자원환경지질, 2023)
The Daum Vent Field (DVF) was newly discovered in the Central Indian Ridge during the hydrothermal expedition by the Korea Institute of Ocean Science & Technology (KIOST) in 2021. In this paper, we describe the detailed mineralogy and geochemistry of hydrothermal chimney and mound to understand the nature of hydrothermal mineralization in the DVF. The mineral assemblages (pyrite±sphalerite±chalcopyrite) of dominant sulfides, FeS contents (mostly <20 mole %) of sphalerite, and (Cu+Zn)/Fe values (0.001-0.22) of bulk compositions indicate that the DVF has an strong affinity with basaltic-hosted seafloor massive sulfide (SMS) deposit along the oceanic ridge. Combined with the predominance of colloform and/or dendritic-textured pyrite and relatively Fe-poor sphalerite in chimneys, the fluid-temperature dependency of trace element systematics (Co, Mn, and Tl) between chimney and mound indicates that the formation of mound was controlled by relatively reducing and high-temperature fluids compared to chimney. The δ34S values (+8.31 to +10.52‰) of pyrite reflect that sulfur and metals were mainly leached from the associated basement rocks (50.6-61.3%) with a contribution from reduced seawater sulfur (38.7-49.4%). This suggests that the fluid-rock interaction, with little effect of magmatic volatile influx, is an important metal source for the sulfide mineralization in the DVF. 다음 열수분출대(Daum Vent Field, DVF)는 한국해양과학기술원 주도로 수행된 2021년도 인도양 중앙해령 대양탐사에서 새롭게 발견되었다. 본 논문에서는 DVF의 광상 유형 분류, 광화 조건 비교 및 주요 금속 공급원 규명을 위해 획득한 침니와 마운드 시료를 대상으로 현미경 관찰, 전암분석, 전자현미분석 및 in situ 황 동위원소 분석을 실시하였다. 유형별 중앙해령 시스템과의 비교연구 결과 DVF에서 확인되는 주요 광물조합(황철석±섬아연석±황동석), 섬아연석 FeS 함량(대부분 <20 mole %) 및 (Cu+Zn)/Fe 전암 구성비(0.001-0.22)의 상관성은 DVF가 현무암 기반의 중앙해령 해저열수광상임을 시사한다. 침니에서 확인되는 교질상/수지상 황철석의 우세한 산출, 상대적으로 철이 결핍된 섬아연석 및 Co 결핍과 Mn, Tl 부화로 특징되는 온도 의존성 금속의 거동 특성은 침니에 비해 마운드의 형성이 상대적으로 고온의 환원성 유체에 의해 규제되었음을 나타낸다. In situ 황 동위원소 분석에서 확인되는 황철석의 δ34S 값 범위(+8.31에서 +10.52‰)는 약 38.7-49.4%의 해수기원 황과 50.6-61.3%의 화성기원 황의 복합적인 기여를 반영하며, 이는 DVF 형성에 있어 주요 금속 공급원이 마그마 영향을 거의 받지 않은 물-암석 상호작용임을 지시한다.